COVID-19 concerns, health services utilisation and social support among Western Australians with diabetes during the pandemic. (December 2021) - Olson, Jenny L; Mergelsberg, Enrique; Jensen, Jessica; Schofield, Deborah; Watson, Natasha
People with diabetes face increased risk of serious COVID-19 complications, making self-care for optimal metabolic management crucial. However, the pandemic has reduced access to routine care among people with diabetes. The pandemic can also elicit distress, which can impact diabetes self-management and health. To understand the impact of COVID-19 on Western Australians with diabetes, we conducted an evaluation involving an online survey of consumers of diabetes health services and an analysis of routine program data (i.e. service utilisation/program attendance). Survey respondents were concerned about contracting COVID-19, many intended to change the way they utilised health services and many indicated they would continue to socially isolate. Utilisation of digital/telephone services peaked between April and June 2020. Despite the concerns indicated, a participation resurgence was observed upon resumption of face-to-face programs. Continued access to diabetes programs via multiple modes of delivery is critical to support optimal self-care and mitigate COVID-19 risks, distress and social isolation. This timely and pragmatic assessment of consumer beliefs synthesised with routinely collected evaluation data represents an agile approach to evaluation through an emerging public health crisis. The findings helped to ensure optimal service delivery to meet the needs of this priority population throughout the pandemic.